Echoes of Affective Stimulation in Brain connectivity Networks. (17th November 2017) - Borchardt, Viola; Fan, Yan; Dietz, Marie; Melendez, Ana Lucia Herrera; Bajbouj, Malek; Gärtner, Matti; Li, Meng; Walter, Martin; Grimm, Simone
Abstract: Affective experience has effects on subjective feelings, physiological indices, entails immediate activity changes in the brain, and even influences brain networks in a protracted manner. However, it is still unclear, how the functional connectivity (FC) interplay between major intrinsic connectivity networks upon affective stimulation depends on affective valence, and whether this is specific for affective experience, i.e., can be distinguished from cognitive task execution. Our study included fMRI scans during and after affective stimulation with sad and neutral movies and a working memory task complemented with measures of cardiovascular activity and mood. Via parcellation of the brain into default mode network (DMN), central executive network (CEN), and dorsal attention network, and application of network-based statistics, we identified subnetworks associated with changing psychological contexts. Specific effects for affective stimulation with negative valence were both reduced heart rate variability and mood, and upregulated FC of inter-CEN-DMN connections while intra-DMN connections were downregulated. Furthermore, results demonstrated a valence-specific dynamic carry-over effect in nodes of the CEN, which temporarily increased their FC strength after affective stimulation with negative valence and exhibited distinct temporal profiles. The reported effects were clearly distinguishable from those of a cognitive task and further elucidate the trajectory of affective experience.